Analyzing and Filtering Multimedia Digital Evidence with Artificial Intelligence (LACCEI, 2024)
Digital evidence has been growing exponentially over the years, not just in size but also in quantity: we now store more files than ever, both on computers and smart devices. The use of multimedia formats has also increased, with audio and video recordings being more prevalent than they previously were. This poses a problem for digital forensic examiners, who now must sift through these files listening to what is said in them. Artificial Intelligence models and applications that can be run locally provide us with a novel way to work with these challenging forms of evidence, drastically reducing the time required to find important information in these ever more present formats, while meeting the stringent requirements of data privacy that laws impose upon investigations.